COMPARATIVE RESEARCHES OF THE HIGH-STRENGTH CAST IRON MICROSTRUCTURE OF AFTER LASER AND PLASMA PROCESSING - V. I. Gurinovich; V. S. Golubev; A. I. Pokrovskiy; I. A. Romanchuk; N. F. Solovey (Литьë и металлургия)
The comparative researches of microstructure of highstrength cast iron after laser and plasma processing are carried out. It is shown that the peculiarity of plasma processing is formation of deeper layers with hardness 950010000 MPa. At laser processing the depth of the strengthened layers is less (about 0,5-0,8 mm), and their hardness is higher (to 11000 MPa).